Predictive modeling of tolerance-dependent failure behavior of self-pierce riveted joints: From coupon-level tests to sub-component validation - Olfert, Viktoria; Yang, Keke; Rochel, Philip; Bähr, Philipp; Hein, David; Sommer, Silke; Meschut, Gerson (Journal of Manufacturing Processes)
Manufacturing tolerances have a measurable influence on the structural integrity of self-piercing riveted (SPR) joints in automotive applications, yet their quantitative impact on load-bearing behavior remains insufficiently resolved. This study establishes a validated hierarchical methodology to predict tolerance-dependent failure behavior of SPR joints, progressing from coupon to sub-component scale through an integrated experimental–numerical approach. Five critical manufacturing tolerances, including rivet length (±0.5 mm), rivet head position (±0.3 mm), orthogonality deviation (2.8° and 5°), lateral offset (up to 1.2 mm), and flange overlap reduction (up to 7.5 mm), were investigated. Steel–steel joints exhibited a higher sensitivity to tolerances by a factor of 2–3 compared to steel–aluminum joints. A unified effective rivet length concept was developed to consolidate the geometric effects of all tolerances into a single physically meaningful parameter, enabling load-bearing capacity prediction with R2 > 0.95 across all evaluated loading directions. The sub-component validation employing T-joint specimens indicates a 2–3 fold amplification of tolerance effects at critical structural regions, providing experimental evidence for the hierarchical scaling principle. The methodology was implemented in a tolerance-dependent CONSTRAINED_SPR3 formulation, providing >99 % computational efficiency improvement while maintaining a deviation in maximum force prediction within ±7 %. This framework enables the physically consistent representation of manufacturing variation within large-scale simulations and establishes a transferable basis for tolerance-resilient virtual vehicle development.

Techniken des wissenschaftlichen Arbeitens im Hochschulstudium. Eine Bestandsaufnahme anhand von Bachelor-Studienordnungen des Unterrichtsfaches Pädagogik in Nordrhein-Westfalen - Engemann, Mario (die hochschullehre)

Warum wir ein Public-Service-Internet brauchen, nicht die Definanzierung öffentlicher Medien - Fuchs, Christian (ORF Public Value Texte)

Experimental characterization and numerical analysis of the influence of the CED coating process on viscous fingering formation in hybrid-jointed mixed structures - Al Trjman, Mohamad; Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Riese, Julia (The Journal of Adhesion)
The joining of dissimilar materials, such as steel and aluminum, entails significant challenges during thermal curing processes due to differing coefficients of thermal expansion. This study addresses the formation of “viscous fingering” instabilities in structural adhesive joints, which are induced by thermally driven relative displacements during the liquid phase of the adhesive. Using a component-like specimen “bridge specimen,” the dependency of this phenomenon on process temperature and structural stiffness (rivet distance) was characterized. Experimental results reveal that while the relative displacement scales cubically with the free buckling length, the resulting adhesive area reduction follows an exponential trend, leading to a loss of effective bond area of up to 79%, which significantly compromises the joint strength in automotive applications. To predict these process-induced defects, a thermo-chemo-viscoelastic-viscoplastic adhesive model implemented in LS-DYNA was applied. The model combines curing kinetics, viscoelastic relaxation, and pressure-dependent plasticity and features a geometric damage parameter (D) that captures the adhesive area reduction caused by viscous fingering as an exponential function of the accumulated normal strain in the liquid phase. This damage parameter, calibrated on base-specimen level, was transferred to the component geometry. The simulation demonstrated high predictive accuracy with a maximum deviation of the adhesive area reduction of 3.1% compared to experimental data. This validates the model’s capability to predict manufacturing-induced damage in complex hybrid structures solely based on thermal boundary conditions.
Keywords: Adhesive area reduction; CED coating process; delta alpha problem; epoxy structural adhesive; influence of manufacture; multi-material design; numerical simulation (FEM); relative displacements; viscous fingering (saffman-taylor-instability).

Increasing the design degree of freedom for polarization through multilayer synchronous polarization projection - Jin, Xiao; Zentgraf, Thomas (Advanced Photonics)
The degrees of freedom (DoFs) of light determine the maximum number of independent signal channels an optical system can support. However, the polarization DoF is intrinsically limited to two by orthogonality, which causes unavoidable crosstalk and often forces position multiplexing, where different channels are assigned to distinct spatial locations to suppress crosstalk. This research introduces a multilayer synchronous polarization projection method that fundamentally increases the DoF for polarization multiplexing. The DoF equals twice the number of projection layers. We experimentally demonstrate six- channel polarization multiplexing holography without position multiplexing. The six-channel multiplexing results indicate that our approach exceeds the conventional polarization multiplexing method, yielding an average 3.79 dB improvement in extinction ratio across the six channels. Compared with the theoretical limit of traditional polarization multiplexing, our method reduces crosstalk by an average of 6.52 dB across all channels in a seven-channel design. The polarization projection method breaks the DoF limitation of polarization multiplexing, opening a path toward high-dimensional photonic information encoding for communication, encryption, and imaging.

Making Corpus Creation in Early Music Rewarding and Effective: Finding the Optimum Between Standardisation and Autonomy - Wiering, Frans; Bergwall, Erik; van Berchum, Marnix; Goebl, Werner; Van Kranenburg, Peter; Lewis, David; Plaksin, Anna Viktoria Katrin; Rodríguez-García, Esperanza; Smith, David J.; Visscher, Mirjam; Weigl, David M.
Several early music projects, such as the Stanford Josquin Project, have demonstrated the potential for attaining valuable new musicological insights using a corpus-based approach. However, the available musical corpora tend to be relatively small and exhibit considerable variation in encoding practices. Aspiring corpus researchers are confronted with a lack of suitable data, which needs to be addressed before they can embark on their proper research. The EarlyMuse Short Term Scientific Mission CORSICA has surveyed the current state of corpus creation and digital editing in early music. Based on this information, it has developed a vision for the future of corpus building in this field, which aims to speed up the production of digital encodings while respecting the autonomy of the encoders and acknowledging their efforts. This is important because much high-quality encoding is carried out outside the field of professional musicology, and engaging citizen scientists could help address the current shortage of research data. The CORSICA team‘s vision is informed not only by a study of the available data, standards and technologies, but also by Human-Computer Interaction, placing human goals and values before the creation of technology and work processes. The core of the vision is that successful corpus creation must be an inclusive endeavour in terms of both technology and human participation. The report concludes with an implementation plan outlining the initial steps required to realise the vision.
Keywords: citizen science; crowdsourcing; digital editions of music; early music; human computer interaction; music corpora; music encoding; musicology

Sexuelle Gewalt an Minderjährigen im Erzbistum Paderborn. Eine historische Untersuchung (1941–2002) - Priesching, Nicole; Hartig, Christine

Responsibilities in sXAI - Rohlfing, Katharina J.; Alpsancar, Suzana; Schulte, Carsten (Social Explainable AI)
Abstract One of the purposes for which XAI is often brought into play is to enable a user to act responsibly. However, responsibility is a complex normative and social phenomenon that we unfold in this chapter. We consider that the classical concepts of agency and responsibility do not fully capture what is needed for meaningful collaboration between human users and XAI. Advocating the perspective of sXAI, we argue that the growing adaptivity of AI systems will result in sXAI being considered as partners. Both partners adopt particular (dialogical) roles within a collaborative process and take responsibility for them. We expect that these roles lead to reactive attitudes toward the sXAI on the side of the human partners that make these roles relational. They resemble those reactive attitudes that we hold toward other human agents. For agents to exercise their responsibility, they need to possess agential capacities to fulfill their role with respect to the structure of a social interaction. Hence, sXAI can be expected to act responsibly. But because of XAI’s limited normative capacities, it might rather act as a marginal agent. We refer to marginal agents and show they can be scaffolded with regard to their agential capacities and their knowledge about the structure of a social interaction. The structure links the actions of the partners to each other in terms of a set of stimuli and responses to it in pursuit of a particular goal. Hence, it is important to differentiate between the different goals that a structure can impose for exercising responsibility. Therefore, we follow (Responsibility from the margins. Oxford University Press; 2015. https://doi.org/10.1093/acprof:oso/9780198715672.24001.0001 ) and offer three structures that can help to organize responsibility for decisions made with the assistance of AI systems. These structures are attributability, answerability, and accountability. Our insights will inform the development and design process of XAI to meet the guiding principles of responsible research and innovation as well as trustworthy AI.

Tasking AI Fairly. How to Empower AI Practitioners With sXAI? - Alpsancar, Suzana; Stamboliev, Eugenia (Social Explainable AI)
Abstract This chapter critically examines how social explainable AI (sXAI) can better support AI practitioners in ensuring fairness in AI-based decision-making. We argue for a fundamental shift: Fairness should be understood not as a technical property or an information problem, but as a matter of vulnerability—focusing on the real-world impacts of AI on individuals and groups, especially those most at risk. Hereby, we call for a shift in perspective: from fair AI to tasking AI fairly . To motivate our vulnerability approach, we review the “Dutch welfare fraud scandal” (system risk indication—SyRI) and current challenges in the field of fair AI/machine learning (ML). Vulnerability of a person or members of a definable group of persons is a complex relational notion, and not a technical property of a technical system. Accordingly, we suggest several nontechnical strategies that hold the promise to compensate for the insufficiency of purely technical approaches to fairness and other ethical issues in the practical use of AI-based systems. To discuss how sXAI, due to its interactive and adaptive social character, might better fulfill this role than current XAI techniques, we provide a toy scenario for how sXAI might support the virtuous AI practitioner in an ethical inquiry. Finally, we also address challenges and limits of our approach.

The Risk of Manipulation and Deception in sXAI - Alpsancar, Suzana; Klenk, Michael (Social Explainable AI)
Abstract XAI can minimize the risks of being manipulated and deceived by AI but in turn entails other specific risks. This also applies to sXAI, and the specifically social character of sXAI harbors particular risks that designers and developers should be aware of. In this chapter, we shall discuss the potential opportunities and risks of sXAI. We see a particularly positive potential in the social character of sXAI, which lies in the fact that skillful users, including those with “healthy distrust,” can use the adaptivity of sXAI to produce an explanation that is actually relevant and adequate for them. However, this requires a high level of skills on the part of the user and is thus in contrast to the general promise of efficiency in the use of AI. A potential risk of XAI is that it can be (even more) persuasive, as the interactive involvement and the anthropomorphism strengthen a trustworthy appearance/performance (independent of the adequacy of the sXAI performance).

Values and Norms in sXAI - Reijers, Wessel; Alpsancar, Suzana (Social explainable AI. Communications of NII Shonan Meetings)

Social Explainable AI
Abstract This introduction sets the stage for the present book. Whereas research in eXplainable AI (XAI) is motivated by societal changes and values, technology development largely ignores social aspects. This book aims to address this research gap with a systematic and comprehensive social view on explainable AI. Besides introducing many relevant concepts, the book offers first access to their possible implementation, thus advancing the development of more social XAI. The introduction starts by connecting the topic to the general research field of XAI. The second part defines the novel approach of social eXplainable AI (sXAI) along the three characteristics of social interaction such as patternedness, incrementality, and multimodality. Finally, the third part explains the structure followed by each chapter. The book offers insights not only for readers who work on technology development but also for those working in sociotechnical fields. Addressing an interdisciplinary readership, the book is an invitation for more exchange and further development of the sXAI field.

Incremental communication - Wrede, Britta; Buschmeier, Hendrik; Rohlfing, Katharina Justine; Booshehri, Meisam; Grimminger, Angela (Social Explainable AI)

Theoretical aspects of multimodal processing - Grimminger, Angela; Buschmeier, Hendrik (Social Explainable AI)

A Note on the Size Reduction Reform in the German Parliament: A Game Theoretic Analysis of Power Indices - Duman, Papatya; Haake, Claus-Jochen (Review of Economics)
Abstract We investigate whether the recently approved reforms of the apportionment of parliamentary seats to parties in the German Bundestag affects the parties’ political influence measured by power indices. We find that under neither reform the underlying simple game, which describes the possibilities to form governments, remains unchanged and as a result the Shapley-Shubik and the Banzhaf index are unaltered. As a consequence, the major change resulting from the reforms is the reduction of the Bundestag’s size to 630 seats.
Keywords: Bundestag reform; Banzhaf power index; Shapley-Shubik power index

Reflexion von individuellen Selbstregulationsfähigkeiten zur Professionalisierung im bildungswissenschaftlichen Begleitseminar des Praxissemesters - Lehberger, Regine (Handlungsorientierung in der Ausbildung von Fachkräften und pädagogischen Fachkräften. Konzeptionen und Forschungsperspektiven)

Characteristics of nonverbal behavior - Lazarov, Stefan Teodorov; Tchappi, Igor; Grimminger, Angela (Social Explainable AI)

Timing and synchronization of multimodal signals in explanations - Wagner, Petra; Kopp, Stefan (Social Explainable AI)

Practices: How to establish an explaining practice - Rohlfing, Katharina J.; Vollmer, Anna-Lisa; Grimminger, Angela (Social Explainable AI)

Scenarios of Social Explainable AI in practice - Främling, Kary; Alami, Rachid; Hulstijn, Joris; Tchappi, Igor; Grimminger, Angela; Wrede, Britta; Buschmeier, Hendrik; Kubler, Sylvain (Social Explainable AI)